The role of imaging and biopsy in the management and staging of large non-pedunculated rectal polyps. (3rd August 2018) - Banerjee, Anjan K; Longcroft-Wheaton, Gaius; Beable, Richard; Conti, John; Khan, Jim; Bhandari, Pradeep
ABSTRACT: Introduction : Endoscopic mucosal resection (EMR) and endoscopic submucosal dissection (ESD) are often used for benign and Sm1 large non-pedunculated rectal polyps (LNPRPs), although other surgical techniques including transanal endoscopic microsurgery (TEMS) and transanal minimal invasive surgery remain available. This review covers the role of pre-excisional imaging and selective biopsy of LNPRPs. Areas covered : Polyps between 2 and 3 cm with favorable features (Paris 1, Kudo III/IV pit patterns, and non-lateral spreading type [LST]) may have a one-stage EMR without biopsy and imaging, provided adequate expertise is available with other technologies such as magnifying chromoendoscopy. Higher-risk polyps (moderate/severe dysplasia, 0–IIa+c morphology, nongranular LST, Kudo pit pattern V or submucosal carcinoma, or those >3 cm) should have pre-EMR/ESD imaging with magnetic resonance imaging (MRI) and/or endorectal ultrasound (ERUS) ± biopsies and photographs prior to multidisciplinary team discussion. Expert commentary : In some centers, EMR and ESD are considered the primary modality of treatment, with TEMS as a back-up, while elsewhere, TEMS is the main modality for excision of significant polyps and early colorectal cancer lesions. Likewise, the exact roles of ERUS and MRI will depend on availability of local expertise, although it is suggested that the techniques are complementary.